2014
DOI: 10.3233/npm-14814005
|View full text |Cite
|
Sign up to set email alerts
|

A survey of fetal care centers in the United States

Abstract: OBJECTIVE: Fetal care centers have recently emerged in affiliation with children's hospitals throughout the United States. Few studies have evaluated this new multidisciplinary model of care. STUDY DESIGN:We conducted a survey of multidisciplinary fetal care centers in the United States; survey data was analyzed using descriptive statistics. RESULTS: 59 centers were identified; 29 centers (49%) returned completed surveys. Most centers are located in a children's hospital (54%), and the majority of centers (76%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…1 An awareness of the patient experience of fetal care has contributed to the development of specialized centers, or fetal care centers, as an alternative to the traditional prenatal care model for the care of families with a diagnosis of a fetal anomaly. 2,3 Fetal care centers consist of multidisciplinary teams who provide fetal diagnosis and consultations for expectant parents. 2,4 These centers, which aim to improve gaps in care quality through coordinated, patient-centered care, typically reside in tertiary care centers.…”
Section: Introductionmentioning
confidence: 99%
“…1 An awareness of the patient experience of fetal care has contributed to the development of specialized centers, or fetal care centers, as an alternative to the traditional prenatal care model for the care of families with a diagnosis of a fetal anomaly. 2,3 Fetal care centers consist of multidisciplinary teams who provide fetal diagnosis and consultations for expectant parents. 2,4 These centers, which aim to improve gaps in care quality through coordinated, patient-centered care, typically reside in tertiary care centers.…”
Section: Introductionmentioning
confidence: 99%
“…Following publication of this landmark trial, there was a rapid increase in the number of centres offering fetal surgery for myelomeningocele (MMC) worldwide. In the United States, a survey of 59 fetal care centres conducted in 2014 showed that nine centres were offering this service. As the response rate was under 50%, this is likely to have been an underestimate.…”
Section: Introductionmentioning
confidence: 99%
“…A recent survey of 29 U.S. fetal care centers demonstrated that the majority are administered by MFM specialists. 19 Although there are undoubtedly more medical centers across the country that likely employ regular Multi-D team care processes, the current lack of a standardized assessment tool makes ascertainment of these processes difficult. With this knowledge gap in mind, we have shown that health care providers involved in a monthly PCC believe Multi-D care approaches to be effective, pragmatic, and may result in improved patient, family, and provider satisfaction.…”
Section: Discussionmentioning
confidence: 99%